2019
DOI: 10.47203/ijch.2019.v31i01.008
|View full text |Cite
|
Sign up to set email alerts
|

Psycho-social health problems: Prevalence and associated factors among students of professional colleges in Jammu

Abstract: Background: Psycho-social health problems are an area of concern worldwide especially among students pursuing professional courses. The competition for grades, carrier insecurity often contribute to various emotional disturbances such as stress, anxiety and depression. Aims and Objectives: to determine the prevalence of stress, anxiety and depression in students of two main professional streams (medical & engineering) and to find out various factors associated with them. Material and methods: A cross-secti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…Moreover, SAD might impact students' cognitive functioning and personal resources, thereby influencing their perceptions of academic control (Pekrun, et al, 2017). Consequently, SAD affects students' academic accomplishments (Kumari, et al, 2019) because they perceive the activity as a threat, debilitating productivity (Tang, et al, 2018). Also, stressed students only focus on past pessimistic experiences and worries about the future (Fagley, 2018).…”
Section: Stress Anxiety and Depressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, SAD might impact students' cognitive functioning and personal resources, thereby influencing their perceptions of academic control (Pekrun, et al, 2017). Consequently, SAD affects students' academic accomplishments (Kumari, et al, 2019) because they perceive the activity as a threat, debilitating productivity (Tang, et al, 2018). Also, stressed students only focus on past pessimistic experiences and worries about the future (Fagley, 2018).…”
Section: Stress Anxiety and Depressionmentioning
confidence: 99%
“…First-year university students drop out more than do students of any other year (Cole, 2017) because emotional and academic-related demands are more significant in college than in school (UL-Haq, et al, 2018). During their transition to higher education, these students experience high levels of stress, anxiety, and depression (SAD), which impact how they perceive academic tasks (Hsu & Goldsmith, 2021) and challenge their cognitive and developmental processes (Kumari, et al, 2019). Thus, students require specific competencies to cope with educational demands and to succeed (Blazquez, et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Based on the previous epidemiological literature, a remarkable proportion of university students are suffering from depression and anxiety [ 7 – 9 ]. Concerning depression in students, its prevalence has changed in different contexts such as 68.5% in Hong Kong [ 10 ], 43.7% in India [ 11 ], 37% in Malaysia [ 12 ], 43% in Saudi Arabia [ 13 ], 63.3% in Egypt [ 6 ], and 27.1% in Turkey [ 14 ]. Similarly, the prevalence of anxiety among students in Hong Kong [ 10 ], India [ 11 ], Malaysia [ 12 ], Saudi Arabia [ 13 ], Egypt [ 6 ], and Turkey [ 14 ] were 54.4%, 68.6%, 63%, 63%, 78.4%, and 47.1%, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Prevalence of depression and other psychiatric symptoms among Pakistani students has also been investigated 11,12,13 . Some studies were reported for Asian and Indian medical students 14,15,16,17 . Factors reported in these studies vary but stressful study schedule, hectic clinical hours, cynicism, worrying for making career and burnouts are commonly reported 18 .…”
Section: Introductionmentioning
confidence: 99%